L’integrità psicofisica della persona nella legislazione e nella giurisprudenza italiane - Cornetti, Ilaria (Il sogno della farfalla, 2016)
An abstract and rational conception of individuals and of fundamental human rights inspires laws and jurisprudence that are “inhuman”, where individuals are reduced to bodies only; the body, which is completely split from non-material reality, becomes the object of aggressive and violent actions as far as it concerns sex changes, voluntary abortions, medically assisted procreation, endoflife care. The principle of the defence of individuals’ psycho-physical integrity, as it abides by the Constitution and truly represents the coexistence of both material and non-material reality within each person, becomes the instrument to write regulatory and juridical approaches that are able to protect human beings and their humanity.